miR-23b Negatively Regulates Sepsis-Induced Inflammatory Responses by Targeting ADAM10 in Human THP-1 Monocytes - Wenying Zhang; Furong Lu; Yuliu Xie; Yao Lin; Tian Zhao; Shoubao Tao; Zhipeng Lai; Ning Wei; Ruoxuan Yang; Yiming Shao; Junbing He (Mediators of Inflammation)
Background. Previous studies have demonstrated pivotal roles of disintegrin and metalloproteinase 10 (ADAM10) in the pathogenesis of sepsis. MicroRNA- (miR-) 23b has emerged as an anti-inflammatory factor that prevents multiple autoimmune diseases. However, the underlying mechanisms of miR-23b in the regulation of ADAM10 and sepsis remain uncharacterized. Methods. The expression levels of ADAM10 and miR-23b were detected by quantitative RT-PCR and western blot analysis. Cytokine production and THP-1 cell apoptosis were measured by enzyme-linked immunosorbent and annexin V apoptosis assays. Bioinformatics analyses and qRT-PCR, western blot, and luciferase reporter assays were performed to identify ADAM10 as the target gene of miR-23b. Results. miR-23b expression was downregulated in the peripheral blood mononuclear cells of sepsis patients and LPS-induced THP-1 cells and was negatively correlated with the expression of ADAM10 and inflammatory cytokines. miR-23b regulated ADAM10 expression by directly binding to the 3′-UTR of ADAM10 mRNA. The overexpression of miR-23b alleviated the LPS-stimulated production of inflammatory cytokines (TNF-α, IL-1β, and IL-6) and apoptosis by targeting ADAM10 in THP-1 cells. The inhibitor or knockdown of ADAM10 elicited effects similar to those of miR-23b on THP-1 cells upon LPS stimulation. Conclusions. The present study demonstrated that miR-23b negatively regulated LPS-induced inflammatory responses by targeting ADAM10. The molecular regulatory mechanism of miR-23b in ADAM10 expression and sepsis-induced inflammatory consequences may provide potential therapeutic targets for sepsis.